Detection of human papillomavirus in organs of upper genital tract in women with cervical cancer. Issue 4 (1st July 2006) - Giordano, G.; D'adda, T.; Gnetti, L.; Froio, E.; Merisio, C.; Melpignano, M.
Abstract : In this study, we evaluated the presence of human papillomavirus (HPV) DNA in organs of the female upper genital tract, using nine hysterectomy and salpingo-oophorectomy specimens affected by HPV-positive invasive cervical carcinomas, to establish if cervical HPV infection can spread to upper tracts of the female genital system. HPV DNA was evaluated by polymerase chain reaction (PCR) in all cervical carcinomas as well as in all tracts of the genital system. Then, these data were compared with the results obtained from PCR study of five other hysterectomy and salpingo-oophorectomy specimens (control cases). The criteria used for selection of the control cases were informed consent of the patients for research at the time of surgery, absence of neoplasms, absence of any anatomic lesion caused by HPV in cervix, and external genitalia. All selected cases were squamous cervical carcinomas. PCR analysis revealed HPV DNA in all cases of cervical carcinoma. The HPV DNA was detected as weak positivity on PCR analysis in other organs of the genital system. However, the distribution of HPV DNA varied in the various cases and in the different tracts of the same hysterectomy and salpingo-oophorectomy specimen. We believe that the HPV DNA, detected as a weakly positive signal, in the upper genital tract of patients who have a cervical squamous carcinoma could be a reflection of a latent HPV infection, as well as a sign of the existence of micrometastases containing HPV DNA, which cannot be detected by conventional histologic techniques.